The segmentation of the Canarian tourism market with regared to expenditure: an empirical study of La Palma - José A. Alvarez-Gonzalez; Flora M. Diaz-Perez; Maria Bethencourt Cejas; M Olga Gonzalez Morales (European Regional Science Association (ERSA), 2002)
In the context of the European Union countries, the Canary Islands have presented and continue to do so, unquestionable comparative and competitive advantages as supplier of tourism products that have lead to, driven more by managerial initiative and foreign capital than by the desire and initiative of the local population, a truly monocultural tourism production. The strong expansion of the services sector that tourism development has produced in parallel constitutes a logical consequence of an activity such as tourism characterised to be basic (Begg, 1993), that is to say, to present very strong effects on other economic activities. It is in fact the economic importance of tourism in the Canary Islands that has lead local authorities to consider the maintenance and improvement of competitiveness levels in tourism in the field of the domestic and international market (Government of Canaries, 1998). The maintenance and improvement of competitiveness levels depend on the segmentation of tourism supply as means of responding to, on one hand, greater competition in prices in the tourist markets of homogeneous products, especially in the sector of sun and beach, and on the other hand, the appearance of an increasing demand for more customised services, where the tourist outlines his/her leisure time requirements in an individual way which ultimately changes the essence of the homogeneous tourist package that the tour-operator has traditionally offered. In this paper we use, therefore, a focus on the segmented markets in which a range of tourism products exists, each one of which satisfies, to greater or lesser extent, the needs of a segment of demand. We have two objectives, firstly, to identify those segments of current demand acquired at destination and, secondly, to determine, amongst them the niches associated with greater expense, in order to profile lines of a regional policy of innovation in products that it embraces them and generates greater levels of local development. Thus we will analyse several sources of data. On the one hand, data which comes from the Survey of Tourist Expenditure carried out by the Institute of Statistics of the Canary Islands and on the other, information obtained in an empirical study carried out over the last few years and referring especially to the island of La Palma. Specifically, we will establish two expenditure segments: lower and middle, to thus determine the characteristics that identify tourists included in the bracket of highest expenditure at destination.
Keywords: 330